Pharmacovigilance Practice: The Current Challenges and the Gaps in the Medical Students’ Curriculum - Mainul, Haque; Abdullahi Rabiu, Abubakar (2016)
Adverse drug reaction is defined by the WHO as a response to a medicinal product which is noxious and unintended, and which occurs at doses normally used in man for prophylaxis, diagnosis, therapy of disease or for the modification of physiologic function. The term Pharmacovigilance was coined by a French group of pharmacologist and toxicologist in the 1970s, which implied strategy promoting detection and assessment of side effects and adverse drug reaction. The first endeavor made to resolve the problem of drug safety was announced in 1961 promptly after the disaster caused by thalidomide treatment in pregnant women. The World Health Organization center for adverse drug reaction monitoring is known as the Uppsala Monitoring Centre. It is an International establishment with the responsibility of coordinating the program based on an agreement made in 1978. The major challenges of Pharmacovigilance program are underreporting, and the best solution is to resolve the problem from the grassroots. This claim could be justified as the outcome of previous knowledge, attitude and practice studies on adverse drug reactions and Pharmacovigilance among medical students was inadequate. Also, the curriculum of teaching and training of medical students was insufficient. The aim of this review was to discuss the current challenges facing adverse drug reactions reporting system and to highlight the gap left in the training of medical students.